Blow-Up Criteria for Three-Dimensional Boussinesq Equations in Triebel-Lizorkin Spaces - Minglei Zang (Discrete Dynamics in Nature and Society)
We establish a new blow-up criteria for solution of the three-dimensional Boussinesq equations in Triebel-Lizorkin spaces by using Littlewood-Paley decomposition.